Clinical application of combined CRP and PCT detection in diagnosing and prognosing fracture-related infections - Liu, Xiaojie; Lian, Jie; Liu, Fei; Han, Dunxin; Sang, Chenglin (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo investigate the clinical significance of combined procalcitonin (PCT) and C-reactive protein (CRP) testing in the diagnosis of fracture-related infections (FRIs).MethodsA retrospective analysis was performed on 252 patients with bone infections admitted between January 2018 and September 2024. CRP and PCT levels were measured in all patients both at diagnosis and postoperatively. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of combined CRP and PCT for diagnosing FRIs were calculated. Based on clinical follow-up data, patients were divided into low-level and high-level groups according to the changes in CRP and PCT levels, and clinical outcomes, including length of hospital stay and infection control, were analyzed.ResultsThe postoperative levels of CRP and PCT in the infection group were significantly higher than in the control group (P < 0.05). The sensitivity, specificity, PPV, and NPV of combined CRP and PCT detection were 90.48%, 96.83%, 96.61%, and 91.04%, respectively. Patients in the high CRP and PCT group had a significantly longer hospital stay compared to the low-level group, and infection control rates were lower. Combined CRP and PCT detection was more effective in diagnosing and predicting clinical outcomes.ConclusionCombined detection of CRP and PCT has high clinical application value in the diagnosis and prognosis evaluation of fracture-related infections, providing more accurate guidance, particularly in predicting recovery and infection control.